Corporate Social Responsibility: Historical Overview and Conceptual Framework - EL BADRI, Lamia; AASRI, Mohammed Rachid; HOUMAIR, Meryem; FAITEH, Anouar (Journal of Environmental Management and Tourism, 2025)
The emergence of unprecedented socio-environmental challenges has highlighted the need for a profound transformation of traditional business models. Corporate Social Responsibility (CSR) has emerged as an essential framework for addressing these challenges, by integrating ethical, social and environmental considerations into business practices. This article explores the evolution and significance of CSR, examining its historical roots, theoretical and conceptual foundations. The study begins by tracing the origins of CSR, exploring its ethical and religious foundations within the broader context of “Business and Society”. It then analyzes the historical development of CSR, highlighting the various conceptual approaches that have shaped its understanding over time. Finally, the article examines the key stages in the evolution of CSR, synthesizing its various definitions into an overarching framework for sustainable business practices.